Sustainable Innovation in Supply Chain Management: A Strategic Approach to Enhance Economic Resilience - Sumartono, Eddy; Suhendar, Suhendar; Ernita, Mahdar (Arbain Publishing, 2024)
This study explores the role of sustainable innovation in enhancing economic resilience through effective supply chain management. Using a qualitative approach with case studies of three large manufacturing companies, the study analyzes how organizations integrate digital technologies, develop adaptation strategies, and build strategic partnerships to achieve sustainability goals while maintaining competitive advantage. The results show that effective implementation of sustainable innovation resulted in a 30% reduction in carbon emissions and a 3.5% increase in operating margins. Supplier collaboration (92% adoption rate) and process digitalization (85%) emerged as key drivers of success, while joint R&D demonstrated the highest impact on sustainability scores (4.7/5.0). These findings highlight the importance of a holistic approach to sustainable supply chain transformation and provide practical insights for organizations seeking to enhance their economic resilience through sustainable practices.